Application of a Malecot drain in the management of a vaginal cuff dehiscence: A case report and review of the literature - Bria Murray; Caleigh E. Smith; Jorge Alsina; Megan Howard; Charles Landen; Paola A. Gehrig (Elsevier, 2024)
Background: Vaginal cuff dehiscence (VCD) in the setting of acute infection is an uncommon but serious complication of total hysterectomy without clear guidelines for management. There is a need for further documentation of best practices around treatment, particularly when it comes to surgical drain utilization and placement. Case description: We present a case of a 68-year-old with primary peritoneal carcinoma who underwent a robot-assisted total laparoscopic hysterectomy as part of an interval debulking surgery and had a VCD. The cuff was repaired vaginally in the operating room with placement of a Malecot catheter for pelvic abscess drainage. Discussion: The literature is sparse in regard to clear guidelines for management of VCD. Surgical and expectant management approaches are dependent on patient stability, surgical experience, local practice norms, and evidence of intra-abdominal injury. Interventional radiology has become a primary source of drain placement in management of VCD and vaginal cuff abscess. Malecot drains are a low cost, and effective intervention for such management and an important resource for the gynecologic surgeon.